2009
DOI: 10.1007/s00787-009-0039-2
|View full text |Cite
|
Sign up to set email alerts
|

Involvement in bullying and depression in a 2-year follow-up in middle adolescence

Abstract: The main objective was to analyse whether involvement in bullying at school predicts depression, and whether depression predicts involvement in bullying in middle adolescence. A total of 2,070 15-year-old girls and boys in two Finnish cities were surveyed at ninth grade (age 15) at schools, and followed up 2 years later in the Adolescent Mental Health Cohort Study (AMHC). Depression was measured by a Finnish modification of the 13-item short Beck Depression Inventory. Involvement in bullying was elicited by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
147
3
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(176 citation statements)
references
References 56 publications
17
147
3
9
Order By: Relevance
“…This is consistent across most previous studies that found unique associations between victimization and non-clinical outcomes after adjusting for prior adjustment problems (Arseneault et al 2006;Kaltiala-Heino et al 2010;Schreier et al 2009;Sugden et al 2010). …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent across most previous studies that found unique associations between victimization and non-clinical outcomes after adjusting for prior adjustment problems (Arseneault et al 2006;Kaltiala-Heino et al 2010;Schreier et al 2009;Sugden et al 2010). …”
Section: Discussionsupporting
confidence: 90%
“…Conversely, internalizing problems may not just be the consequences but also, although weak, the antecedents of victimization (r=.08) -a reciprocal influence, which may lead to a vicious circle (Kaltiala-Heino et al 2010;Sweeting et al 2006). This further illustrates the importance of controlling for internalizing symptoms which predate the onset of victimization in study designs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents who were severely victimized showed an increased risk of severe symptoms of certain mental health problems. Compared with other studies that have relied on victimization and exposure to bullying assessed at a single point in time, 8,[31][32][33] our trajectory analyses have the advantage of identifying patterns of victimization varying in severity and over time, highlighting a general decline in victimization with age.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35][36] Psychotic experiences Being bullied increased the risk of psychotic experiences. Also a dose-response relationship was found where stronger associations were identified with increased frequency, severity and duration of being bullied.…”
mentioning
confidence: 99%